2015
DOI: 10.1128/jvi.00305-15
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Human Cytomegalovirus Infection in CD34+Hematopoietic Cells and Derived Langerhans-Type Dendritic Cells

Abstract: Acquisition of human cytomegalovirus (CMV) usually occurs by contact between contaminated bodily fluids, such as urine and saliva, and host mucosal cells. Langerhans-type dendritic cells (LC) are the only type of immune cells found in the outermost layers of the oral mucosae, where they not only provide a first line of defense against CMV but can easily be targeted by orally administered vaccines, while their bone marrow resident progenitors are important sites of virus latency. In this work, we tracked the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 64 publications
(114 reference statements)
6
27
0
Order By: Relevance
“…Previous work has demonstrated that HCMV can establish latency in primary hematopoietic cells [6, 9, 38–47] as well as in Kasumi-3 cells [4850]. Here, we first determined whether the NR-1 clinical strain can achieve latent infection in CD34 + hematopoietic progenitor cells (HPCs) and Kasumi-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that HCMV can establish latency in primary hematopoietic cells [6, 9, 38–47] as well as in Kasumi-3 cells [4850]. Here, we first determined whether the NR-1 clinical strain can achieve latent infection in CD34 + hematopoietic progenitor cells (HPCs) and Kasumi-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…A further complication to understanding the latent program has been the multitude of culture systems used to study latency. One broadly used yet nonstandardized approach with regards to media and cytokine composition is stromal-free culture systems with exogenously supplied cytokine cocktails designed to either maintain CD34 + phenotypes or promote differentiation down a particular lineage (3741). While the ease of this approach is appealing, cytokine concentrations and combinations can result in aberrant differentiation or expansion of cells that have little physiological relevance to function in vivo .…”
Section: Latent Reservoirsmentioning
confidence: 99%
“…The capacity of laboratory strains to establish latency is controversial. Previous reports (60, 72, 81) and well as more recent publications (37, 41, 68, 114) have carried out latency studies using laboratory-adapted strain (AD169 or Town var RIT 3 ) infection in HPCs (CD34 + or CD33 + GMPs). While few side-by-side comparisons have been made, the baseline replication of a laboratory-adapted strain (in the absence of a reactivation stimulus) is 10- to 100-fold greater than that of low-passage strains in THP-1 (68) and CD34 + HPCs (47), respectively.…”
Section: Viral Genomesmentioning
confidence: 99%
“…Thus, HCMV can establish latent infection in PB-CD34 cells and appears to modulate immune molecules. 42,44 HCMV latently infected PB-CD34 cells are more susceptible to HIV-1 infection Because AIDS progresses faster in HCMV-seropositive individuals, we next examined if latently infected PB-CD34 cells can favor HIV-1 infection. HCMV or mock infection of PB-CD34 cells at day 5 PI were infected by HIV-1 NL4-3 (X4-tropic; X4-HIV).…”
Section: Establishment Of Hcmv Latent Infection In Pb-derived Cd34mentioning
confidence: 99%